Language and the development of facial emotion perception during childhood - Koh, Ken Wen (2018)
In contrast to common beliefs that language only possesses expressive function in emotions, facial emotion perception may have a deeper connection with language. The universality hypothesis of emotion perception was rejected in multiple research when manipulating subject’s language capacity. This research review attempts to understand the association between language acquisition and facial emotion perception, specifically during childhood when most of the key developments take place. The literature is systematically arranged according to the methodological approaches, i.e. longitudinal and cross-sectional approach respectively. From the developmental perspective, temporal association was found between language acquisition and improvement in perceptual ability of facial emotion expression. When comparing typical developing children with others (minority language-speaking, language-impaired, hearing-impaired and psychopathological), language, despite non- conclusive, was found to exert different level of influence on the facial emotion perception. Integration of findings from different studies leads to our suggestion that conceptual knowledge and ToM might act as the mediators within the language-facial emotion perception link. To further define the relationship, this paper ends by suggesting a few future research directions. For instance, the inclusion of bilingual subjects and more realistic facial emotion recognition test.